Cognitive and emotional functioning in binge‐eating disorder: A systematic review. Issue 6 (26th May 2015) - Kittel, Rebekka; Brauhardt, Anne; Hilbert, Anja
ABSTRACT Objective Binge‐eating disorder (BED) is characterized by recurrent episodes of binge eating and is associated with eating disorder and general psychopathology and overweight/obesity. Deficits in cognitive and emotional functioning for eating disorders or obesity have been reported. However, a systematic review on cognitive and emotional functioning for individuals with BED is lacking. Method A systematic literature search was conducted across three databases (Medline, PubMed, and PsycINFO). Overall, n = 57 studies were included in the present review. Results Regarding cognitive functioning (CoF), individuals with BED consistently demonstrated higher information processing biases compared to obese and normal‐weight controls in the context of disorder‐related stimuli (i.e., food and body cues), whereas CoF in the context of neutral stimuli appeared to be less affected. Thus, results suggest disorder‐related rather than general difficulties in CoF in BED. With respect to emotional functioning (EmF), individuals with BED reported difficulties similar to individuals with other eating disorders, with a tendency to show less severe difficulties in some domains. In addition, individuals with BED reported greater emotional deficits when compared to obese and normal‐weight controls. Findings suggest general difficulties in EmF in BED. Thus far, however, investigations of EmF in disorder‐relevant situations are lacking. Discussion Overall, the cross‐sectional findings indicate BED to be associated with difficulties in CoF and EmF. Future research should determine the nature of these difficulties, in regards to general and disorder‐related stimuli, and consider interactions of both domains to foster the development and improvement of appropriate interventions in BED.